A theoretical and experimental study of the crystal structure of H2V3O8. Issue 129 (16th December 2015) - Mettan, Yoann; Caputo, Riccarda; Chatterji, Tapan
Abstract : The present study aims at clarifying the positions of hydrogen atoms in H2 V3 O8 . Abstract : The present study aims at clarifying the positions of hydrogen atoms in H2 V3 O8 . Starting with the structure provided by Oka ( J. Solid State Chem., 1990, 89, 372) a model was established using first-principles total energy calculations. Optimized structure data were obtained for two possible configurations within the orthorhombic symmetry representation of the V–O frame. The hydrogen atoms were located close to the oxygen atom labelled O(6) by Oka, in a water-like H–O–H moiety. The two different configurations are distinguished by either parallel or perpendicular orientation of the H–O–H plane with regards to the crystallographic b -axis. In addition, neutron diffraction measurements at 4 K and ambient temperature were performed. The hydrogen atom positions were found in proximity of O(6), in a similar arrangement as predicted theoretically. In particular, the structure obtained from the analysis of the 4 K data matches the model with H–O–H plane parallel to the b -axis.